Strategi Politik Calon Independen dalam Pemilihan Kepala Daerah Kota Samarinda Tahun 2020 - Hizkiadven Sanggam Batara Lebang; Iman Surya; Letizia Dyastari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The purpose of this study was to find out the political strategy of independent candidates in the regional head elections in Samarinda City in 2020. The data collection techniques used were observation, interviews, documentation, and secondary data. The data collection technique uses a qualitative descriptive model put forward by Miles and Huberman. This research was conducted in Samarinda City. The research focus is product, promotion, place, price. The results of the study show that there are several strategic patterns used by independent candidates, namely the 4p, namely political product (Product), Promotion (Promotion), Place (Place), Price (Price). The first is a political product made by independent candidates to attract attention. from the people in political products there is a vision and mission as well as excellent programs that will be carried out if elected as regional heads. Many people who are quite interested in independent candidates can be seen from the independent candidates asking for support from the public until at the time of the vote count in the local elections where the independent candidates garnered 51,652 supports and when the elections were held the independent candidates managed to collect 98,245 votes. They also carried out promotions for Attracting public attention, there are several methods used by independent candidates, namely using billboards, banners, online media, and face to face places. Independent candidates visit people in traditional markets to ask for support, and for budget prices provided by independent candidates Rp. 667,000,000 consisting of independent candidates' personal funds of Rp. 560,000,000 and donations from other parties of Rp. 107,000,000.